A Noradrenergic Lesion Attenuates Surgery-Induced Cognitive Impairment in Rats by Suppressing Neuroinflammation - Wang, Jiayu; Zhou, Ying; Li, Ke; Li, Xiaofeng; Guo, Meimei; Peng, Mian (Frontiers in Molecular Neuroscience, 2021)
Postoperative cognitive dysfunction (POCD) is a common postoperative neurocognitive complication in elderly patients. However, the specific pathogenesis is unknown, it has been demonstrated that neuroinflammation plays a key role in POCD. Recently, increasing evidences has proved locus coeruleus noradrenergic system (LCNE) participates in regulating neuroinflammation in some neurodegenerative disorders. We hypothesize that LCNE plays an important role in the neuroinflammation of POCD. In the present study, DSP-4 400μg was injected intracerebroventricularly for each rat on 7 days before anesthesia/surgery to deplete locus coeruleus noradrenaline. We applied a simple laparotomy and brief upper mesenteric artery clamping surgery as the rat POCD model. The open field test, novel objection and novel location recognition, and Morris water maze were performed to assess the postoperative cognition. High performance liquid chromatography (HPLC) was used to measure the level of noradrenaline in plasma and brain tissues, and immunofluorescence staining was applied to evaluate the activation of microglia and astrocyte. We also used ELISA to assess the level of inflammatory cytokines and BDNF. Pre-treatment of DSP-4 decreased the levels of systemic and central NE, increased the level of IL-6 in plasma at 6 hours after surgery, and decreased the level of IL-1β in plasma, prefrontal cortex and hippocampus on 1 week postoperatively. In addition, DSP-4 treatment attenuated hippocampal dependent learning and memory impairment in POCD rats, with downregulation of the activation of microglia and astrocyte in prefrontal cortex and hippocampus. In conclusion, these findings give evidence of the effects of LCNE in modulating neuroinflammation in rats with POCD and provide a new perspective in the prevention and treatment of POCD.